Automated trucks and the future of logistics: A Delphi-based scenario study - Svenja Escherle; Emilia Darlagiannis; Anna Sprung (Logistics Research, 2023)
The logistics industry is facing a transformation. Automated driving has been gaining importance in the commercial vehicle industry and trucks with SAE L4 are expected by 2030 for the hub-to-hub scenario. Driven by the research question of what the direct logistics environment of automated trucks will look like in 2030 a two-round Delphi-based scenario study was conducted for domestic goods transport in Germany. 19 projections were developed and evaluated by 27 experts from different industries. With completelinkage clustering, four logistics scenarios for 2030 were created. The results show that environmental and social sustainability as well as digitalization are expected to be the most important drivers. These include the shift to electric drive systems, improved working conditions, and increasing transparency and connectivity of the supply chain. The experts forecast an increase in the importance of software services and a continuing shortage of skilled workers. Rather controversial are the topics of charging infrastructure for electrified transport and the degree of automation of loading systems. Overall, the results provide a reliable basis for strategic decision-making in order to ensure the introduction of automated trucks into the logistics of the future and their surrounding environment.
Keywords: 650; Automated Trucks; Future; Logistics; Trends; Delphi Study; Delphi-based Scenario Study